Evaluation of portal venous gas detected by ultrasound examination for diagnosis of necrotising enterocolitis. Issue 3 (11th September 2008) - Dördelmann, M; Rau, G A; Bartels, D; Linke, M; Derichs, N; Behrens, C; Bohnhorst, B
Abstract : Background: Early diagnosis of necrotising enterocolitis (NEC) is difficult but essential for timely therapy. The diagnostic hallmarks and specific radiological signs for NEC are pneumatosis intestinalis (PI) and portal venous gas (PVG), but PVG in abdominal ultrasound (PVG-US) has been proposed as an effective tool in the diagnosis of NEC as well. Objective: To prospectively assess the value of PVG-US for the diagnosis of NEC. Methods: The study screened 352 neonates for PVG-US (n = 796 routine examinations) and performed 48 additional screenings in 34/352 neonates with suspected (stage I, n = 28) or definite NEC (stage ⩾II, n = 20). Sensitivity and specificity of PVG-US for detection of NEC were computed by using NEC stage ⩾II as the reference standard. Results: PVG-US was only present in cases of suspected or definite NEC. The study observed PVG-US in 4/28 NEC stage I and in 9/20 NEC stage ⩾II episodes corresponding to a 86% specificity and a 45% sensitivity for diagnosis of NEC stage ⩾II. However, 7/20 patients with NEC stage ⩾II showed intraoperative findings other than NEC and another 3/20 infants presented with radiologically unspecific intestinal dilatation. None of these 10 infants had detectable PVG-US. Thus, with application of specific radiological signs the sensitivity of PVG-US for diagnosis of NEC stage ⩾II increased to 90%. Conclusion: Screening for PVG-US is a useful, easy and quick bedside test with a high specificity for NEC. Moreover, these results question the value of the Walsh criteria in the diagnosis of NEC.